2022
DOI: 10.3390/ijerph19127327
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and Recommendations for Advancing the Occupational Therapy Workforce Research Worldwide: Scoping Review and Content Analysis of the Literature

Abstract: Occupational therapy workforce research can help determine whether occupational therapists exist in sufficient supply, are equitably distributed, and meet competency standards. Advancing the value of occupational therapy workforce research requires an understanding of the limitations and recommendations identified by these investigations. This scoping review and content analysis synthesizes the study limitations and recommendations reported by the occupational therapy research worldwide. Two independent review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…1. A recent, multi‐pronged scoping review synthesized the global occupational therapy workforce research: studies, 6 findings, 3 limitations & recommendations 7 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1. A recent, multi‐pronged scoping review synthesized the global occupational therapy workforce research: studies, 6 findings, 3 limitations & recommendations 7 …”
Section: Resultsmentioning
confidence: 99%
“…In the context above, the Strengths and Weaknesses of our SWOT framework were primarily identified from the findings of our recent scoping review of the occupational therapy workforce research. The three‐pronged scoping review addressed: (1) the scope of the literature and its research methods, 6 (2) the types of findings generated, 3 and (3) the self‐reported limitations and recommendations 7 . Data and reports generated by WFOT were also used to inform the Strengths and Weaknesses, for example, data from the WFOT human resources project 3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context above, the Strengths and Weaknesses of our SWOT framework were primarily identified from the findings of our recent scoping review of the occupational therapy workforce research. The three-pronged scoping review addressed: 1) the scope of the literature and its research methods, 17 2) the types of findings generated, 18 and 3) the self-reported limitations and recommendations. 19 Data and reports generated by WFOT were also used to inform the Strengths and Weaknesses, e.g., data from the WFOT human resources project, and secondary analyses using this information that is internal to the occupational therapy workforce research ecosystem 3,5,8,26 .…”
Section: Drafting the Swotmentioning
confidence: 99%
“…17 Second, we identified the types of findings that were generated by the occupational therapy workforce research worldwide, including trends in topics across nations. 18 Lastly, limitations and future recommendations reported by the included papers were summarized and identified as possible facilitators or barriers for the strengthening of the occupational therapy workforce. 19 In this short communication , we aim to build on this acquired knowledge, as well as on findings of an external environmental scan and feedback provided by experts, to perform a situational assessment of the development of occupational therapy workforce and its research -toward informing a global human resources strategy for strengthening the profession.…”
Section: Introductionmentioning
confidence: 99%